Comparative analysis of concurrent and sequential chemoradiation in locally advanced lung cancer: a single institution experience - Srivastava, Shelly; Saini, Surendra Kumar; Agarwal, S. K. (International Journal of Research in Medical Sciences, 2019)
Background: Outcome of various treatment regimen are dismal in non-small cell lung cancer. This analysis is done to find possible care in authors institutional set up and to see how these protocols have effect in Indian patients in term of toxicity. Methods: Medical records and data on patients who had been diagnosed with non-small cell lung cancer histologically or cytologically, and who had been treated with sequential chemoradiation and concurrent chemoradiation at the hospital from January 2007 to March 2015 was retrospectively reviewed and analyzed. Two groups of sequential chemoradiotherapy and concurrent chemoradiotherapy were formed and compared for outcomes. Results: Of the 114 evaluable patients in sequential chemoradiotherapy group, the median survival time was 16.0 months and the 1, 3- and 5-years overall survival were 57.0, 26.9 and 21.2%, respectively. Median progression free survival (PFS was 13.0 months and the 1, 3 and 5 years PFS were 52.6, 14.6 and 7.8%, respectively. In concurrent chemoradiotherapy group (105 patients), the overall median survival time was 15 months and the 1, 3- and 5-year overall survival were 56.2, 20.6 and 14.7%, respectively. Median PFS was 13 months and the 1, 3 and 5-year PFS were 48.8, 19.7 and 10.3%, respectively. Grade 3 and 4 toxicity in both regimen groups are same and statistically not significant. Conclusions: Analysis confirm dismal outcome with standard treatment and signifies to search for care beyond conventional chemoradiotherapy.